2012
DOI: 10.21061/jcte.v28i1.572
|View full text |Cite
|
Sign up to set email alerts
|

District Superintendent Perceptions of Idaho Secondary CTE Teachers’ Professional Development Needs

Abstract: The purpose of this study was to describe Idaho superintendents' perceptions of Career and Technical Education (CTE) teacher's professional development needs. A descriptive instrument based on Borich's (1980) Needs Assessment Model was completed by 78 respondents (n = 78). Items related to teaching in a CTE program were assessed for importance, as well as competence of teachers towards the item. Mean Weighted Discrepancy Scores (MWDS) were used to prioritize perceived professional development needs. Teaching c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…Pre-service teacher education programs should expand instruction related to funding sources for local programs, and additional professional development workshops should be available during CTE summer conference and as coursework which can be applied toward certification and advanced degrees (L. L. Moore & Swan, 2008). The results of this study were similar to results from other program areas in the state (Cannon, Kitchel, & Duncan, 2012;Cannon, Kitchel, Tenuto, et al, 2012;Kitchel et al, 2009), indicating the need for CTE teacher education and in-service training to be coordinated across program areas and offered in collaboration with colleges, universities and professional organizations to meet professional development needs of beginning teachers in agricultural education.…”
Section: Conclusion Recommendations and Implicationssupporting
confidence: 72%
See 3 more Smart Citations
“…Pre-service teacher education programs should expand instruction related to funding sources for local programs, and additional professional development workshops should be available during CTE summer conference and as coursework which can be applied toward certification and advanced degrees (L. L. Moore & Swan, 2008). The results of this study were similar to results from other program areas in the state (Cannon, Kitchel, & Duncan, 2012;Cannon, Kitchel, Tenuto, et al, 2012;Kitchel et al, 2009), indicating the need for CTE teacher education and in-service training to be coordinated across program areas and offered in collaboration with colleges, universities and professional organizations to meet professional development needs of beginning teachers in agricultural education.…”
Section: Conclusion Recommendations and Implicationssupporting
confidence: 72%
“…Several of the items across categories were related to organization of the instructor both in and out of the classroom as hygiene factors identified by the Herzberg Motivational Hygiene Theory (Herzberg et al, 1959) regarding work and organizational environment and supported previous research: volume of work (Mundt & Connors, 1999); time management (Mundt & Connors, 1999;Myers et al, 2005;Stair et al, 2012); communication (Myers et al, 2005); classroom management skills (Cannon, Kitchel, & Duncan, 2012;Cannon, Kitchel, Tenuto, et al, 2012;Garton & Chung, 1996;Joerger, 2002;Myers et al, 2005;Nesbitt & Mundt, 1993;Robinson & Edwards, 2012;Ruhland & Bremer, 2002;Stair et al, 2012); paperwork (Stair et al, 2012); budgets (Kitchel, Cannon, & Duncan, 2009); work/life balance (Myers et al, 2005); program planning and prioritization (Garton & Chung, 1996); state level forms and documents (Garton & Chung, 1996;Kitchel et al, 2009); and recruiting students (Stair et al, 2012). The areas of concern identified were also categorized based on the Herzberg's Motivational-Hygiene Theory (Herzberg et al, 1959) as either Motivational or Hygiene factors.…”
Section: Conclusion Recommendations and Implicationssupporting
confidence: 70%
See 2 more Smart Citations
“…Beyond preservice teaching opportunities, the use of professional development (PD) opportunities for our in-service teachers in all phases of their professional careers has been shown to be beneficial (Cannon et al 2013. Investigating the reasons and obstructions that keep in-service teachers from participating in professional development, concluded that the two most prevalent obstacles are time and financial resources.…”
Section: Statement Of the Problemmentioning
confidence: 99%